Variant Analysis of FOXE1 Gene in Non-Syndromic Cleft Lip and Palate Patients of Peshawar, Pakistan (Molecular Medicine Communications, 2023)
One of the most common structural birth defects is the cleft lip and palate, having an incidence rate of 1:700 live births worldwide. It can be isolated cleft lip, isolated cleft palate or a combination of both cleft lip and palate. The orofacial cleft can be caused by a variety of genetic and environmental factors or through an interaction between these factors. The gene Fork-head Box protein E1 (FOXE1) has been documented to be involved with cleft lip and palate. The present study aims to screen mutations in FOXE1 and to correlate phenotype and genotype of affected individuals. After obtaining ethical approval, peripheral blood samples were collected from 100 affected individuals, irrespective of age and gender. The genomic DNA was extracted, followed by quality control through spectrophotometer and gel electrophoresis. Polymerase chain reaction (PCR) was carried out to perform the targeted Sanger sequencing of FOXE1 gene. A point mutation (c.274C>T, rs3021526) in FOXE1 gene was detected in 15 samples. Based on phenotype, males and isolated cleft palate type was commonly involved,with  bilateral occurrence, and moderate cases were frequently seen among the enrolled patients. In this study, a missense substitution was observed in gene FOXE1. This study provides a foundation for genetic counseling for families at risk and offer valuable insights for prevention and management plans.
Keywords: Cleft lip and palate; FOXE1 gene; Pakistani population